EXPERIMENTAL STUDY ON THE USE OF SHARP INFRARED SENSOR FOR DISTANCE DETECTION IN PARKING ASSISTANCE APPLICATIONS IN AUTOMOTIVE SYSTEMS - Paramasatya, Johanes Dimas; Saputri, Fahmy Rinanda (IJISCS (International Journal of Information System and Computer Science), 2023)
In this study, experiments were conducted on the implementation of the Sharp Infrared Sensor, specifically the Sharp 0A4ISK model, for distance detection in parking assistance applications within automotive systems. The increasing complexity of modern vehicles and the need for enhanced parking safety have prompted the exploration of innovative sensor technologies. In this research, we focused on the application of the Sharp Infrared Sensor to improve parking assistance systems. The study involved calibration, testing, and performance evaluation of the sensor on a laboratory scale. The methodology included the design of electronic component circuits and program development. Subsequently, testing of the sensor's ability to accurately detect distances between a miniature vehicle and a wall was performed. The research results indicate that the Sharp Infrared Sensor offers the ability to detect distance, thus holding the potential for integration into automotive systems.